EU After COVID-19: An Opportunity for Policy Coordination - Antonia Díaz; Luis A. Puch (Intereconomics, 2021)
Despite all the difficulties inherent to our political organisation, the European Union has taken a bold step by doubling the EU budget for the next six years with the NGEU fund.
Keywords: 330; Wirtschaftspolitik; Finanzpolitik; EU-Staaten